The management of liver trauma. Issue 714 (April 1985) - Macfarlane, R.
Abstract : Despite advances in the management of liver trauma during the past 40 years, haemorrhage has remained the commonest cause of death. This article outlines the diversity of opinion between the desire to determine the extent of damage and resect devitalised tissue with its attendant risk of exacerbating haemorrhage, and the alternative of a more conservative approach.